Evaluasi Kinerja Pelayanan dan Tarif Sistem Angkutan Umum Berbasis Bus di Kota Semarang (Studi Kasus : Bus Trans Semarang Koridor I Rute Terminal Penggaron – Terminal Mangkang) - Mira Lestira Hariani; Varadila, Vanny; Mukhlis, Jafar (Siklus : Jurnal Teknik Sipil, 2023)
Service quality and fares are very important parameters in the operation of the public transport system. BRT Trans Semarang is a bus-based public transportation system in Semarang city that is operated to overcome congestion and accommodate the movement of people in Semarang City. This study aims to evaluate the service performance and fares of BRT Trans Semarang and to determine the level of user satisfaction. The methods used in this study are observation, interviews, questionnaires and primary surveys. The data obtained is processed, analyzed and all indicators are evaluated referring to the Technical Guidelines for Organizing Public Transport in Urban Areas in the Fixed and Regular Routes of the Director General of Land Transportation 2002. The results show that: 1) overall the performance of BRT Trans Semarang services has met the standards , and there are 2 (two) indicators that doesn't meet the standards, are the average loading factor (utilization factor) and passenger waiting time; 2) Most passengers are satisfied with BRT Trans Semarang services; 3) The exixting fare applied is below the amount of the cost operation issued by the operator so it needs Government support (subsidies) to ensure BRT Trans Semarang can continue operate.